Text difficulty effect on metacognitive reading strategy use among EFL learners - Jafarigohar, Manoochehr; Khanjani, Amin (Penerbit UKM, 2014)
Reading is one of the most integral academic skills in learning a foreign language. According to Anderson (2003), it is the interaction of four factors: the reader, the text, fluent reading and strategic reading. A large number of studies have indeed recognized the importance of the metacognitive reading strategies (MRSs) and text difficulty in reading comprehension. However, the effect of text difficulty on the learners' MRSs use has not been paid due attention in the literature. Accordingly, this study, employing a within-subject design, investigated the effects of text difficulty on MRSs use. Sixty Iranian intermediate EFL learners from two private institutes were asked to answer the Metacognitive Awareness of Reading Strategies Inventory questionnaire (Mokhtari & Reichard, 2002) at three different times, focusing on pre-intermediate (KET), intermediate (PET), and upper intermediate (FCE) texts. To get a better picture of the EFL learners' MRSs, an oral interview was also carried out on 10 participants. The results of the statistical analyses showed that text difficulty had significant effect on metacognitive reading strategy use with problem-solving strategies being affected most. The interview data revealed that the participants in this study benefited from various MRSs such as planning, summarizing and translating especially when the text was difficult. The implications of the study concern foreign language teaching, teacher training and curriculum design with regard to the selection of appropriate reading materials and methodology for EFL learners. Moreover, EFL instructors need to consider the difficulty level of reading materials so as to trigger the learners’ metacognitive reading strategy use.